2023
DOI: 10.1021/acsomega.3c06454
|View full text |Cite
|
Sign up to set email alerts
|

Nonuniform STM Contrast of Self-Assembled Tri-n-octyl-triazatriangulenium Tetrafluoroborate on HOPG

Sergii Snegir,
Yannick J. Dappe,
Dmytro Sysoiev
et al.

Abstract: We have assembled 4,8,12-tri-n-octyl-4,8,12-triazatrianguleniumtetrafluoroborate (TATA-BF4) on highly oriented pyrolytic graphite (HOPG) and have studied the structure and tunneling properties of this self-assembled monolayer (SAM) using scanning tunneling microscopy (STM) under ambient conditions. We show that the triazatriangulenium cations TATA+ form hexagonally packed structures driven by the interaction between the aromatic core and the HOPG lattice, as evidenced by density functional theory (DFT) modelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…For example, XPS and scanning tunneling microscopy (STM) studies of SAMs comprising TATA-based carbocation components have shown these can lose BF4ions upon surface adsorption. 6,74,75 In these reports it was noted that the loss of counterions implied a significant charge transfer to the substrate, 6 and that ion dissociation may be favored by the electric field generated at an STM tip. 75 Supporting computational experiments revealed that while a TATA + -BF4ion pair is stabilized by adsorption on a gold surface, the cohesive energy of the system is reduced by addition of an electron (as we also show above).…”
Section: Additional Discussionmentioning
confidence: 99%
“…For example, XPS and scanning tunneling microscopy (STM) studies of SAMs comprising TATA-based carbocation components have shown these can lose BF4ions upon surface adsorption. 6,74,75 In these reports it was noted that the loss of counterions implied a significant charge transfer to the substrate, 6 and that ion dissociation may be favored by the electric field generated at an STM tip. 75 Supporting computational experiments revealed that while a TATA + -BF4ion pair is stabilized by adsorption on a gold surface, the cohesive energy of the system is reduced by addition of an electron (as we also show above).…”
Section: Additional Discussionmentioning
confidence: 99%